EDUKASI KESEHATAN TENTANG SADARI PADA SUAMI DAN ISTRI - Wirawan, Alfonsius Ade; Fernandez, Gratsia Victoria; Kambey, Stefan Andrew Glorious Pelealu (Jurnal Abdi Insani, 2024)
Early detection of breast cancer is one of the efforts made to identify as early as possible the signs and symptoms of breast cancer. One way to detect breast cancer early is Breast Self-Examination (BSE). Unfortunately, BSE behavior by wives is low. This can be due to lack of knowledge, limited resources and lack of support from husbands in BSE behavior. Therefore, it is necessary to educate wives and husbands. The purpose of this community service activity is to increase knowledge and support from  husbands and wives about BSE behavior through education. So that BSE behavior is formed in wives. Education is carried out in three different places. The media used in this activity are: (1) Book; (2) Leaflet; (3) Video; (4) Power point; and (5) Teaching Aids. The counseling was attended by 60 people consisting of husbands and wives. This activity was conducted in the aula Perum Pemda (Posyandu) Puskesmas Ranomut, in the Puskesmas Tuminting, and in the Lingkungan 5 Kelurahan Tuminting. The entire activity was attended by 60 respondents. During the activity, respondents seemed enthusiastic about the topic presented. The results of the evaluation of the respondents' pre-test scores were that the average value of respondents' knowledge was at point 4.58. However, after education was carried out, the average value of respondents' post-test knowledge was at point 6.20. This shows that there was an increase in the average value of respondents' knowledge by 1.62. From the results of the evaluation of the pre-post test questionnaire, a significant increase in respondents' knowledge about BSE was also obtained (p value <0.05).  BSE education is important in early detection of breast cancer. Optimal use of media can improve respondents' understanding of BSE